A Comprehensive and Reproducible Comparison of Cryptographic Primitives Execution on Android Devices - Aleksandr Ometov (IEEE Access, 2021)
With technology evolving rapidly and proliferating, it is imperative to pay attention to mobile devices’ security being currently responsible for various sensitive data processing. This phase is essential as an intermediate before the cloud or distributed ledger storage delivery and should be considered additional care due to its inevitability. This paper analyzes the security mechanisms applied for internal use in the Android OS and the communication between the Android OS and the remote server. Presented work aims to examine these mechanisms and evaluate which cryptographic methods and procedures are most advantageous in terms of energy efficiency derived from execution time. Nonetheless, the dataset with the measurements collected from 17 mobile devices and the code for reproducibility is also provided. After analyzing the collected data, specific cryptographic algorithms are recommended to implement an application that utilizes native cryptographic operations on modern Android devices. In particular, selected algorithms for symmetric encryption are AES256 / GCM / No Padding; for digital signature – SHA512 with RSA2048 / PSS, and for asymmetric encryption – RSA3072 / OAEP with SHA512 and MGF1 Padding.